Molecular epidemiology of carbapenem-resistant enterobacteriaceae - Li, Zhen (The University of Hong Kong (Pokfulam, Hong Kong), 2013)
﻿Dissemination of Carbapenem-Resistant Enterobacteriaceae (CRE) has raised a new challenge for health organizations all over the world. Acquisition of carbapenemase genes is the most worrisome among these CRE isolates. This study was constructed to investigate the dissemination of CRE isolates in Hong Kong and also to characterize plasmids harboring carbapenemase genes. CRE isolates were collected from public hospitals in Hong Kong from August 2006 to June 2012. Antimicrobial susceptibility of all CRE isolates was tested using disc diffusion method. Screening of carbapenemase genes (blaNDM , blaKPC, blaIMP, blaVIM and blaOXA-48) and ESBL genes (blaCTX-M and blaSHV) were also performed. Clonal relatedness was studied by multi-locus sequence typing. Characterization of plasmids was carried out by conjugation, S1-PFGE, hybridization and plasmid replicon typing. A total of 69 CRE isolates were collected including 50 K. pneumoniae, 15 E. coli, 2 E. cloacae, 1 E. aerogenes and 1 C. freundii. Eighteen carbapenemase producing Enterobacteriaceae were isolated from different patients with travel histories among these 69 isolates. Four K. pneumoniae were detected to carry blaKPC genes on different transferable plasmids as follows: 50 kb, IncX3 plasmid (ST258); 70 kb, un-typeable plasmid (ST258); 130 kb, un-typeable plasmid (ST11) and 140 kb, un-typeable plasmid (ST11). blaIMP genes were also detected in four CRE isolates to be harbored by different plasmids or located on chromosome: ST11 K. pneumoniae (50 kb, IncN), ST1 K. pneumoniae (150 kb, IncA/C), E. cloacae (130 kb, IncN-L/M) and ST899 K. pneumoniae (chromosomal located).